Akuntabilitas dan Transparansi Laporan Keuangan Partai Politik di Indonesia - Oktaviana, Sonya; Amarullah, Fitriani; Anggraita, Viska; Bachtiar, Emil (Universitas Muhammadiyah Metro, 2025)
PThis article is devoted to accountability and transparency of political party financial report in Indonesia, to review the compliance of preparing financial report as stated in regulations, and accordance relevant accounting standard. This is qualitative research using secondary data, analyzing political party financial report; as public entity receiving allocation from national budget. The result shows that majority of political party have not prepared financial report, or have prepared financial report but not audited yet. Novelty of this research is analyzing political party financial report comprehensively, refer to relevant regulation, and accounting standard. Contribution of this research is to recommend alternative ways to cope with regulation and accounting standard weaknesses